2015
DOI: 10.1016/j.alcohol.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional enantioselective effects of the GABAB receptor agonist baclofen in two mouse models of excessive ethanol consumption

Abstract: The GABAB receptor agonist baclofen has been studied extensively in preclinical models of alcohol use disorders, yet results on its efficacy have been uncertain. Racemic baclofen, which is used clinically, can be broken down into separate enantiomers of the drug. Baclofen has been shown to produce enantioselective effects in behavioral assays including those modeling reflexive and sexual behavior. The current studies sought to characterize the enantioselective effects of baclofen in two separate models of etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 45 publications
2
25
2
Order By: Relevance
“…Further, Agmo and Paredes [45, 46] demonstrated that while baclofen reduced sociosexual behavior and locomotion, other drugs also decreased locomotion without affecting sociosexual behavior, suggesting that reductions in locomotor activity are not causative of reductions in motivated behavior. Using home-cage locomotor activity boxes, our lab has recently demonstrated that systemic administration of R(+)- and S(-)-baclofen do not alter locomotor activity during ethanol or saccharin consumption in the same 5 day DID paradigm used in the current study [47]. Thus, our results, taken with those of Spano et al and Agmo and Paredes, suggest that baclofen is working to reduce ethanol consumption via mechanisms alternative to those producing sedation.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Further, Agmo and Paredes [45, 46] demonstrated that while baclofen reduced sociosexual behavior and locomotion, other drugs also decreased locomotion without affecting sociosexual behavior, suggesting that reductions in locomotor activity are not causative of reductions in motivated behavior. Using home-cage locomotor activity boxes, our lab has recently demonstrated that systemic administration of R(+)- and S(-)-baclofen do not alter locomotor activity during ethanol or saccharin consumption in the same 5 day DID paradigm used in the current study [47]. Thus, our results, taken with those of Spano et al and Agmo and Paredes, suggest that baclofen is working to reduce ethanol consumption via mechanisms alternative to those producing sedation.…”
Section: Discussionsupporting
confidence: 75%
“…Working to overcome negative drug effects to consume saccharin would explain why animals drank even after receiving R(+)-baclofen, but it does not explain why S(-)-baclofen did not produce an increase in saccharin consumption or why aCSF reduced saccharin intake. Further, our lab has observed reductions in saccharin intake following systemic R(+)-baclofen [47], so concluding that R(+)-baclofen is unable to reduce saccharin consumption would seem unsatisfactory. Perhaps, the best explanation is that the NACsh is not responsible for the control of saccharin intake, likely due to a combination of a transfer of control to another brain region and the possible lack of dopamine response on Day 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 32 animals were administered 0, 0.75, 1.5, or 3 mg/kg of mecamylamine. Doses were based on previous ethanol DID findings (Hendrickson et al, 2009; Kasten et al, 2015). On day 5, drug was administered immediately prior to bottles on and a fluid intake was monitored at bottles-on, hour 1, and hour 2 to observe time-specific effects on intake.…”
Section: Methodsmentioning
confidence: 99%
“…Mecamylamine is often used to precipitate nicotine withdrawal whereas baclofen attenuates the negative effects of nicotine withdrawal (Varani et al, 2014). Both of these drugs reduce ethanol intake in the DID paradigm and baclofen has been shown to reduce smoking behavior in a clinical trial (Franklin et al, 2009; Hendrickson et al, 2009; Kasten et al, 2015; Leggio et al, 2015). Finally, we sought to characterize whether B6 mice would co-consume nicotine and alcohol, as is often the case in human addiction (National Institute on Alcohol Abuse and Alcoholism, 2007), and whether co-consumption could be pharmacologically manipulated.…”
Section: Introduction1mentioning
confidence: 99%